2018
DOI: 10.1371/journal.pone.0192566
|View full text |Cite
|
Sign up to set email alerts
|

Context or composition: How does neighbourhood deprivation impact upon adolescent smoking behaviour?

Abstract: Neighbourhood effects studies have demonstrated an association between area deprivation and smoking behaviour whereby people living in deprived neighbourhoods are more likely to smoke than those in non-deprived neighbourhoods. This evidence though is based largely upon data that ignores long term exposures to neighbourhood contexts and is confounded by neighbourhood selection bias. In this study, we investigate the temporal ordering of exposure to neighbourhood deprivation throughout childhood and whether asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 40 publications
2
17
0
Order By: Relevance
“…[5][6][7] The appropriateness of using different measures of economic or relational neighbourhood disadvantages (e.g., neighbourhood deprivation or social cohesion) as proxies for each other, or as mediators in different neighbourhood mechanisms, thus depends on the time-point (in cross-sectional studies) or period of life course (in longitudinal studies) under study and the constructs of interest. Our study further extends prior neighbourhood trajectory analyses, [54,55] which…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…[5][6][7] The appropriateness of using different measures of economic or relational neighbourhood disadvantages (e.g., neighbourhood deprivation or social cohesion) as proxies for each other, or as mediators in different neighbourhood mechanisms, thus depends on the time-point (in cross-sectional studies) or period of life course (in longitudinal studies) under study and the constructs of interest. Our study further extends prior neighbourhood trajectory analyses, [54,55] which…”
Section: Discussionsupporting
confidence: 82%
“…In addition, a previous study of ALSPAC data which used the 2004 Indices of Multiple Deprivation identified the same four trajectory groups, demonstrating some robustness in our findings. [55] We did not have access to participants' continuous deprivation scores (e.g., for the income or employment domains), which would have allowed us to analyze greater heterogenity and may have partly driven some of the observed divergence with the perceived measures. We favoured an analysis of neighbourhood deprivation exposure as a dichotomized rather than quintiled variable to conceptualize a threshold of more severe neighbourhood deprivation.…”
Section: Limitationsmentioning
confidence: 99%
“…This was also found in a study using another neighbourhood characteristic, deprivation. 112 Taken together, these findings suggest that, although a direct effect of legislation can be immediate, indirect effects through social networks can continue the impact on adolescent tobacco and smoking awareness for years after, highlighting the need to continue to emphasise reducing parental smoking in tobacco control policy. In conclusion, the POS ban may have disrupted the link between tobacco retailer density and brand awareness and perceived smoking prevalence.…”
Section: Discussionmentioning
confidence: 90%
“… Coleman (1988) considered that a family with high SES can provide a better living environment and more educational resources for their child or children. For example, with a longitudinal data of 2744 adolescents, Morris et al (2018) found that children from low SES families tended to live in low SES neighborhoods, causing a higher tendency for them to take up smoking. With the Independent Freshman Admission administrative data from an elite university (i.e., Peking University in China), Liu et al (2014) found that adolescents in high SES families had more chances to pass the selection process to enter these universities.…”
Section: Introductionmentioning
confidence: 99%